Pengaruh Pemberdayaan Dan Kepercayaan Terhadap Loyalitas Guru SMA Swasta di Kecamatan Pulogadung Jakarta Timur (2018) - Ester Widyati; Mukhneri -; Nurjannah - (Peneliti.net, 2018)
The objective research is to obtain information concerning to the effect of empowerment and trust toward loyalty. The research was conducted by using survey method with path analysis in testing hypothesis. In this research, 148 from 234 teachers selected random sampling. The research was focused on three aspect; empowerment and trust toward loyalty. The data were colected with questionnaire and analyzed with path analysis. Result on the analyisis it is conculated that (1) there the positive direct effect of empowerment towards loyalty, (2) there is positive direct effect of trust towards loyalty and (3) there is positive direct effect of empowerment towards trust.